RETROSPECTIVE CASE CONTROL STUDY OF CANINE EHRLICHIOSIS AT THE VETERINARY FACULTY OF UNIVERSIDAD NACIONAL MAYOR DE SAN MARCOS: 2002-2005 PERIOD - Contreras S., Ana María (2009)
Canine ehrlichiosis is a worldwide well known infectious disease and potentially lethal to dogs and other members of the Canidae family. It is caused by Ehrlichia canis and transmitted by the brown dog tick Rhipicephalus sanguineus. The aim of this work was to carry out a retrospective case-control study in order to evaluate the risk factors associated with the presence of canine ehrlichiosis in dogs that have been patients at the Clinic of Small Animals and at the Clinical Pathology Laboratory of the Veterinary Faculty, San Marcos University, Lima. For this purpose, cases (dogs with ehrlichiosis: n=50) as well as controls (dogs without ehrlichiosis: n=100) from clinical records in the period of 2002-2005 were used. Data was grouped by breed, sex, age, history of tick presence, and home location. Chi square, odds ratio (OR), and logistic regressions were performed. Among the cases, 50% were of large breeds, 72% were males, 64% were ³2 years old, and 82% had ticks. The risk factors associated with the disease were large breeds (OR=12.8, p=0.024), German Shepherd dog (OR=12.2, p<0.01), age (³2-4 years: OR= 4.0, p=0.008) and tick history [82% (48/50) for the cases and 1% (1/100) for the controls].